CHILE HACIA UN DESARROLLO INCLUSIVO - Infante B., Ricardo; Sunkel, Osvaldo (La Sociología en sus Escenarios, 2010)
Abstract. In this paper it is recommended that Chile must adopt a new long term strategy of development that leads to an inclusive development with increasing fairness, in order to surpass the no desirable effects of the type of effective economic growth, that is to say, the persistence of an unacceptable inequality of the income, the levels and the quality of life, as well as the increasing sensation of social exclusion. In order to approach these subjects, first is the evolution of the inequality in the two last decades. Next, the characteristics of the productive structure of the Chilean economy are analyzed, that consider a determining factor of the inequality. From this analysis, the general lineaments of a new long term strategy set out that include the different productive and social layers explicitly from the growth process. Finally, the policy areas are indicated that would be a key to obtain an inclusive development. Resumen. En este trabajo se sugiere que Chile debe adoptar una estrategia de desarrollo renovada de largo plazo que conduzca a un desarrollo inclusivo con equidad creciente, a fin de superar los efectos no deseables del tipo de crecimiento económico vigente, esto es, la persistencia de una inaceptable desigualdad de los ingresos, de los niveles y de la calidad de vida, así como la creciente sensación de exclusión social. Para abordar estos temas, primero se muestra la evolución de la desigualdad en las dos últimas décadas. A continuación, se analizan las características de la estructura productiva de la economía chilena, que se consideran un factor determinante de la desigualdad. A partir de este análisis, se proponen los lineamientos generales de una estrategia renovada que incluya explícitamente los diferentes estratos productivos y sociales del proceso de crecimiento. Finalmente, se señalan las áreas de política que serían clave para lograr un desarrollo inclusivo.